EFFECTIVENESS OF ENDOVENOUS LASER ABLATION IN THE MANAGEMENT OF RECURRENT VARICOSE VEINS OF THE LOWER EXTREMITIES - Minavarkhujayev Ravshankhuja Rahmatkhuja ugli (Modern American Journals, 2025)
Objective To evaluate the clinical effectiveness, safety, and long-term outcomes of endovenous laser ablation (EVLT) in patients with recurrent varicose veins of the lower extremities involving the great saphenous vein (GSV) basin.
Keywords: Recurrent varicose veins, endovenous laser ablation, perforator veins, duplex ultrasound, quality of life.